The rupture in Hong Kong cinema: Post-2000 Hong Kong cinema(s) as both a transnational cinema and a national cinema - Chen, Fangyu (Lumina, 2020)
This paper traces artistic and ideological discrepancies between the young generation of Hong Kong filmmakers and their predecessors – the established generation who contributed to the glory days of Hong Kong cinema during its economic boom. By tracing studies of national cinema and transnational cinema in the last three decades, the author argues that current Hong Kong cinema has split into two: a transnational cinema represented by the established generation of filmmakers; and a national cinema that is driven by the emerging generation who struggles for better preservation of Hong Kong local culture and their own cultural identities. To conduct the research, 47 people were interviewed including13 established filmmakers, 16 young filmmakers and18 film students from 3 universities in Hong Kong. The three groups of respondents generally represent three perspectives: that of the established film practitioners, who have a vested interest in the current co-production era; that of the emerging young film practitioners, who above all crave a flourishing local film market and whose productions exhibit stronger Hong Kong cultural identities; lastly, that of the, who were predominantly born in the 1990s and have the most extreme views against mainland China and whose filmmaking ideologies and practices foreshadow the future of the industry.